Macromedia flash MX 2004 : certified designer study guide. - English, James, ....- (Berkeley : Macromedia, 2005)
With support for CSS, predefined Behaviors, Timeline effects, and more, Flash MX 2004 is a must-have program for your Web design toolbox. Equally essential is the Macromedia certification that proves to your clients that you have the skills to use it effectively! This comprehensive yet easily digestible study guide represents the surest route to getting that seal of approval! Designed specifically to simplify preparation for Macromedia's certification exam (and organized like the exam itself), this volume offers everything intermediate and advanced Flash designers need to know to prove their Flash chops. You'll learn how to identify requirements as well as how to design, construct, and optimize Flash animations with maximum efficiency. Best of all, this essential information is conveyed in clear, direct language complimented by well-explained code examples, loads of sample questions, and plenty of graphics. Also included are extensive notes, tips, and cautions, and the companion Web site provides tips, reading material, and sample tests to help you gauge your exam readiness.
Keywords: Animatietechnieken; Flash; Informatiesystemen; Internet